ANALYSIS OF GARDENING PROBLEMS OF HIGHWAYS AND STREETS - Ткаченко, І. В.; Сердюк, К. В.; Нестеренко, С. В. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper identified and classified roads landscaping elements. Also, the comparative analysis of Ukraine’s regulatory documentsand several foreign countries regardingthe placement of landscaping elements roads and streets, which will help to improve the methodology of design improvement of the road environment. Keywords:classification, gardening, planting road, roads, accommodation options, landscaping.